2019
DOI: 10.3390/ijms20184432
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Lysosomes in a Broad Disease-Modifying Approach Evaluated across Transgenic Mouse Models of Alzheimer’s Disease and Parkinson’s Disease and Models of Mild Cognitive Impairment

Abstract: Many neurodegenerative disorders have lysosomal impediments, and the list of proposed treatments targeting lysosomes is growing. We investigated the role of lysosomes in Alzheimer’s disease (AD) and other age-related disorders, as well as in a strategy to compensate for lysosomal disturbances. Comprehensive immunostaining was used to analyze brains from wild-type mice vs. amyloid precursor protein/presenilin-1 (APP/PS1) mice that express mutant proteins linked to familial AD. Also, lysosomal modulation was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 88 publications
(133 reference statements)
1
35
0
Order By: Relevance
“…It has been reported that APP protein can be degenerated through both the proteasomal and lysosomal pathways [53] and inhibition of lysosomal or proteasomal degradation processes will cause the accumulation of APP fragments and Aβ production. Consistently, enhancing lysosomal cathepsin activity ameliorates Aβ toxicity [54,55] and restoring the autophagy-lysosomal pathway reduced Aβ accumulation and rescued memory performance [56]. These studies suggest that APP traffic to lysosomes may reduce the APP protein level and Aβ production.…”
Section: Discussionmentioning
confidence: 66%
“…It has been reported that APP protein can be degenerated through both the proteasomal and lysosomal pathways [53] and inhibition of lysosomal or proteasomal degradation processes will cause the accumulation of APP fragments and Aβ production. Consistently, enhancing lysosomal cathepsin activity ameliorates Aβ toxicity [54,55] and restoring the autophagy-lysosomal pathway reduced Aβ accumulation and rescued memory performance [56]. These studies suggest that APP traffic to lysosomes may reduce the APP protein level and Aβ production.…”
Section: Discussionmentioning
confidence: 66%
“…In cell-free assays, the carboxypeptidase activity of CatB did not produce C-terminally truncated Aβ peptide variants from Aβ 1-42 that were shorter than 38 or 37 amino acids (Mackay et al, 1997 ; Mueller-Steiner et al, 2006 ). Correspondingly, Butler et al ( 2011 ) and Hwang et al ( 2019 ) reported that the pharmacological modulation of lysosomes and thereby increased levels and activity of CatB resulted in a decrease of Aβ 42 and an increase of Aβ 38 in APPswe/PSEN1dE9 mice. We can only speculate, why we did not observe a shift toward Aβ 1-42 after CatB inhibition with CA-074 Me or deletion of CTSB in H4 APP751 cells in our study.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, the overexpression of APP751 might also lead to an aberrant trafficking and/or C-Terminal truncation. The work of Butler et al ( 2011 ) and Hwang et al ( 2019 ) suffers from a similar dilemma, as they use transgenic animal models: The use of the so-called Swedish mutation of APP and the PSEN1dE9 mutation in both of the animal models should result in a pattern of secreted Aβ with abnormal high percentages of Aβ 1-42, because the Swedish mutations increases the affinity of APP for BACE1 cleavage and the PSEN1dE9 mutations reduces the inherent carboxypeptidase activity of the γ-secretase. Conversely, the lower amount of APP and the unrestricted carboxypeptidase activity of the γ-secretase could be the reason why lysosomal CatB was apparently not involved in the degradation of Aβ in primary chicken and human astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…NCAM species add to the list of synaptic proteins that are reduced by RDX detonations and are also known to display substantial declines in AD patients and animal models (11,16,35). While moderate and severe TBI have been previously associated with increased dementia risk, it is of particular interest that mild TBI without loss of consciousness was recently linked to dementia as well, with more than a two-fold increase in the risk of dementia diagnosis (36).…”
Section: Discussionmentioning
confidence: 99%